Onion pollenkitt: Function, DNase activity, fatty acid composition, and SEM imaging - Majd Mardini; Aleksey Ermolaev; Alexey Yu. Kuznetsov; Alexey V. Zhevnerov; Sergey Buravkov; Ludmila Khrustaleva (PLoS ONE, 2025)
Pollenkitt, a sticky substance produced by the tapetal cells of pollen grains, plays a crucial role in pollen functionality, yet it remains an understudied component in plant biology. In this study, we investigated the role of pollenkitt in onion (Allium cepa) pollen, focusing on its effects on pollen germination, DNase activity, fatty acid composition, and ultrastructure. Our findings reveal that pollenkitt is essential for successful onion pollen germination and tube growth on the stigma, as its removal significantly inhibited these processes. Additionally, we demonstrated that onion pollenkitt exhibits DNase activity, degrading plasmid DNA in a concentration-dependent manner, with EDTA effectively inhibiting the degradation. Gas chromatography identified 20 fatty acids in pollenkitt, with a predominance of unsaturated fatty acids. Using scanning electron microscopy (SEM), we showed structural differences between pollen grains with and without pollenkitt, and we observed the process of pollenkitt removal from the surface of pollen grains by water washing. These results offer valuable insights for future research aimed at optimizing pollen-mediated gene-editing systems and highlight the importance of considering pollenkitt in such applications.